Stability of the anterior arm of three different Hyrax hybrid expanders: an in vitro study - Gonzalo de la Iglesia; André Walter; Fernando de la Iglesia; Heinz Winsauer; Andreu Puigdollers
ABSTRACT Introduction: The force applied to the teeth by fixed orthopaedic expanders has previously been studied, but not the force applied to the orthodontic mini-implant (OMI) used to expand the maxilla with Hyrax hybrid expanders (HHE). Objective: The aim of this article was to evaluate the clinical safety of the components (OMI, abutment and double wire arms) of three different force-transmitting systems (FTS) for conducting orthopaedic maxillary expansion: Jeil Medical & Tiger Dental™, Microdent™ and Ortholox™. Methods: For the realization of this in vitro study of the resistance to mechanical load, three different abutment types (bonded, screwed on, and coupling) and three different OMIs' diameters (Jeil™ 2.5 mm, Microdent™ 1.6 mm and Ortholox™ 2.2 mm) were used. Ten tests for each of these three FTS were carried out in a static lateral load in artificial bone blocks (Sawbones™) by a Galdabini universal testing machine, then comparing its performance. Comparisons of loads, deformations and fractures were carried out by means of radiographs of FTS components in each case. Results: At 1- mm load and within the elastic deformation, FTS values ranged from 67 ± 13 N to 183 ± 48 N. Under great deformations, Jeil & Tiger™ was the one who withstood the greatest loads, with an average 378 ± 22 N; followed by Microdent™, with 201 ± 18 N, and Ortholox™, with 103 ± 10 N. At 3 mm load, the OMIs shaft bends and deforms when the diameter is smaller than 2.5 mm. The abutment fixation is crucial to transmit forces and moments. Conclusions: The present study shows the importance of a rigid design of the different components of HHEs, and also that HHEs would be suitable for maxillary expansion in adolescents and young adults, since its mean expansion forces exceed 120N. Furthermore, early abutment detachment or smaller mini-implants diameter would only be appropriate for children.